Throwing velocity and jump height in female water polo players: Performance predictors - McCluskey, L.; Lynskey, S.; Chak Kei Leung; Woodhouse, D.; Briffa, K.; Hopper, D. (Journal of Science and Medicine in Sport, 2010)
Throwing velocity and vertical jumping ability are essential components for shooting and passing in water polo. The purpose of this study was to determine whether there is a relationship between throwing velocity and water jump height in highly skilled female water polo players. Throwing velocity and head height at ball release were measured in twenty-two female players (age 20.41 years (6.16); weight 68.28 kg (8.87)) with two 50 frames per second cameras while shooting at goal. Water jump height was also measured with a modified Yardstick® device. Multiple regression analyses showed that peak lower limb powerwas the most significant predictor of maximal velocity. Power alone accounted for 62% of the variance in maximum velocity (p < 0.001). Once power was entered into the model none of the other physical characteristics (lean mass, fat mass, land jump height and anthropometry) made a significant contribution to throwing velocity. After controlling for the effect of power, head height at ball release accounted for an additional significant proportion of the variance in maximal velocity (R2 change 7%; p = 0.049). Lower body power was a significant predictor of higher throwing velocity in highly skilled female water polo players. Players with relatively higher underlying levels of lower limb power who are able to generate greater elevation out of thewater are able to throw the ball faster.